COVID-19 AND THE FUTURE OF ZOOS - Pepper, Angie; Voigt, Kristin (Les ateliers de l'éthique / The Ethics Forum, 2021)
The COVID-19 crisis has left zoos especially vulnerable to bankruptcy, and the precarity of their financial situation threatens the lives and well-being of the animals who live in them. In this paper, we argue that while we and our governments have a responsibility to ensure the protection of animals in struggling zoos, it is morally impermissible to make private donations or state subsidies to zoos because such actions serve to perpetuate an unjust institution. In order to protect zoo animals without perpetrating further injustice, governments should subsidize the transformation of zoos into sanctuaries and then facilitate the gradual closure of most of these sanctuaries.